KEMAMPUAN TRANSLASI REPRESENTASI MATEMATIS DITINJAU DARI STUDENT BELIEF PADA MATERI TEOREMA PYTHAGORAS - Kurniawati, Tri; Hartoyo, Agung; Sayu, Silvia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to describe student’s translation ability on mathematical representation in terms of student belief in the Pythagoras theorem material of sets in grade VIII SMP Negeri 19 pontianak. The method that was use in this research is descriptive method with case study form. The subject of this research are 32 students. The data collection instrument that used is written test in essay, questionnaire, and interview as the follow-up activity. The result of data analylisis showed that the students’ translation ability on mathematical representation is classified as very low, six types of translation that might occur translation ability on mathematical representation from the symbol representation to the visual representation is classified  highest and translation  ability on mathematical representation from the visual to the verbal representation is classified lowest. Keywords: Translation Ability on Mathematical Representation, Student Belief, Pythagoras Theorem.